103 High rates of venous and arterial thrombotic events in POEMS patients. Issue 6 (27th May 2022) - Keddie, Stephen; Sayar, Zara; Weatherill, Anna; Sive, Jonathan; Thomas, Mari; D'Sa, Shirley; Lunn, Michael
Abstract : Background: Arterial and venous thrombotic events occur in patients with POEMS (Polyneuropathy, Organomegaly, Endocrinopathy, M-protein, Skin changes) syndrome with a previously reported rate of 20%. We reviewed the UK POEMS Registry to describe the rate of venous thromboembolism (VTE), arterial events and risk factors. Methods: The UK POEMS Registry is the largest single-centre cohort in Europe and comprises 100 patients. Data were collected on arterial and venous thrombotic events from 1999 to present day. Results: Of the 83 assessable patients, median age at presentation was 52 years. Twenty-five patients expe- rienced 35 clinically apparent arterial or venous events. Eleven patients had 14 VTEs including deep vein thrombosis (DVT, 4/14), pulmonary embolism (4/14) and peripherally inserted central catheter-associated DVT occurring during autologous stem cell transplant (4/14). Sixteen patients experienced 21 arterial events: stroke (7/21), peripheral arterial occlusion (6/21), myocardial infarction (4/21) and microvascular disease (2/21), with no discernible relationship with thrombocytosis or polycythaemia. The combined venous and arterial event rate was 42%, over double that previously reported. There were more arterial than venous events, and most occurred during active pre-treated disease indicating a need for a pre- emptive approach to thromboprophylaxis. Conclusion: Arterial and venous thromboses are more common in POEMS syndrome than previously reported and appear associated with disease pathology and activity. We propose a management strategy for appropriate thromboprophylaxis in POEMS patients throughout the course of disease. stephen.keddie@nhs.net